Mortalidade e consumo de espécies de lagartas em milho e soja Bt - Dallagnol, Lilian Cris (2016)
Spodoptera frugiperda, Pseudaletia sequax and Helicoverpa armigera (Lepidoptera: Noctuidae) are among the main pests in corn and soybeans. This characteristic can be attributed to its polyphagia and continuous food supply in the system, associated with agricultural intensification. The continued suited and adoption of integrated pests management strategies, in time and space, is essential to minimize the negative effects that these species have caused in Brazilian agriculture. Genetically modified plants resistant to insects represent a significant improvement in these lepidopteran control approaches, since they express genes from the bacterium Bacillus thuringiensis (Berliner) (Bt) that encode entomotoxic proteins. However, the effectiveness of control of different Bt toxins has not been sufficiently explored and compared. Therefore, this study aimed to evaluate the effect of Bt proteins in different species of caterpillars, aiming control efficiency. Three experiments were conducted in a controlled field and environment using Bt and non-Bt genotypes and three species of caterpillars: S. frugiperda and P. sequax in corn and H. armigera in soybean. In Bt corn, the incidence and severity of caterpillars of S. frugiperda is lower in MON89034 x TC1507 x NK603 technology relationg to other evaluated. For P. sequax, the mortality of third and fifth instar carterpillars is higher in MON89034 x TC1507 x NK603 corn technology. This specie dies quickly when it feeds with Bt, Bt11 x MIR162 x GA21 and MIR162 corn technology. Bt corns less consumed by P. sequax caterpillars are those with the MIR162 and Bt11 x MIR162 x GA21 technologies. The plant structure (new leaf, old leaf and pods) that serves as food for caterpillars in Bt soybean does not influence the mortality of first instar H. armigera. In fourth instar caterpillars, mortality is higher in young leaves. In pods, the mortality of neonate caterpillars is higher. The neonate caterpillars of H. armigera fed with Bt soybean die more quickly than fourth instar caterpillars.